Effects of tamoxifen-loaded erythropoietin-coated nanostructured lipid carrier on breast cancer cells and rat mammary gland tumour - Beh, Chaw Yee (2019)
Nanomedicine is an emerging and fast developing area in the medical field, especially in the treatment of cancers. Most chemotherapy drugs have the limitation of poor drug water solubility which hinders their drug efficacy. The incorporation of drugs into nanoparticulated carriers had improved the low water solubility and efficacy of antibreast cancer drugs. In this study, the nanostructured lipid carrier (NLC) was loaded with tamoxifen (TAM) and coated with erythropoietin (EPO) to produce EPOTAMNLC, and the anticancer effects of this drug delivery system was determined. For comparison the TAM-loaded NLC (TAMNLC) was also developed. These nanoparticulated carriers were produced by using the high pressure homogeniser method and physiochemically and morphologically characterised using the dynamic light scattering technique, zetasizer, and transmission electron microscopy. The thermodynamic interaction between EPO and TAMNLC was investigated through the fluorescent spectroscopy and isothermal titration calorimetry while their binding efficiency was obtained through sodium dodecyl sulfate polyacrylamide gel electrophoresis. The elucidation of oestrogen and erythropoietin receptors status on MCF-7 and LA7 cells was determined through immunocytochemistry staining. The cytotoxic effect, mode of cell death and cell cycle arrest caused by treatment with EPOTAMNLC and TAMLC toward MCF-7 and LA7 cells was determined by the 3-(4,5- dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and flow cytometry. The in vivo effects of EPO-TAMNLC and TAMNLC were determined in the normal and mammary gland tumour rats by using doses 1.25 mg/kg BW, 2.5 mg/kg BW and 5 mg/kg BW and treated through intravenously. The rat mammary gland tumour was induced by injecting 6 × 106 LA7 cells into the mammary fat pad. Toxicity parameters included serum kidney and liver function parameters and the histology of the kidneys, liver, heart, lungs, spleen, and bone marrow. The EPO-TAMNLC formulation was stable with particle size of 55.39±0.98 nm, zeta potential of -1.58±0.47 mV, and polydispersity index of 0.19±0.01. Based on ultrastructural analysis, the nanoparticles were spherical. The binding interaction of EPO and TAMNLC shown was spontaneous with positive enthalpy. It was shown the binding efficiency of EPO to TAMNLC was highest at pH 7.2 at 55.43%. The immunocytochemistry staining revealed that these cells are positive for oestrogen (ER) and erythropoietin receptors (EpoRs). The in vitro toxic effect of EPO-TAMNLC and TAMNLC on MCF-7 and LA7 cells was timedependent with the GI50 of 4.8 μM, 5.1 μM, 2.5 μM and 2.5 μM respectively which postulated to occur through the targeting of the ER and EpoRs in the cancer cells. However, both drug carrier systems did not significant (P>0.05) affect the viability of the normal MCF-10A and HDFa cells. Flow cytometry study showed that EPOTAMNLC induced apoptosis and G0/G1 cell cycle arrest in the cancerous MCF-7 and LA7 cell lines. For the in vivo part, normal rats treated with intravenous EPO– TAMNLC and TAMNLC did not show evidence of toxicity from the treatments, suggesting that EPO-TAMNLC and TAMNLC are safe for parenteral use and the LD50 exceed 5 mg/kg BW. Both EPO-TAMNLC and TAMNLC, while significantly (p<0.05) reducing the mammary gland tumour size in rats, achieved sustain antitumour effect and are more effective anti-tumour agents than oral TAM. In conclusion, EPO-TAMNLC is a promising targeted anticancer drug formulation for treatment of ER-positive breast cancers.